الــتــنمــية السيـاحية الـــمستدامة فــي الجــزائر - حضري, فضيل; تلمسان, جامعة (Sciences de l'Homme et de la Société, 2014)
تهدف هذه الدراسة إلى إبراز دور السياحة في التنمية باعتبارها نشاطًا ضروريًا لحياة الشعوب، وتأثيرها المباشر على مختلف القطاعات، فالاهتمام الدولي بالسياحة لم يكن وليد الصدفة، أو التكهنات، إنما كان مرتكزًا على إيمان راسخ لدى المجتمع الدولي بمنظماته ومؤسساته المختصة بأن السياحة من خلال ما ستحدثه من اتصالات مباشرة وعفوية غير متأثرة بوسائل الإعلام، بين رجال ونساء ينتمون لثقافات مختلفة، ويتبعون أساليب حياة متباينة، تمثل قوة حيوية لإحلال السلام، وعاملاً لتعزيز الصداقة والتفاهم بين شعوب العالم، وعاملاً بمنطق التوفيق بين حماية البيئة والتنمية الاقتصادية، ومحاربة الفقر على نحو مستدام. Abstract: This study aims to highlight the role of tourism in development as a necessary activity to people's lives, and their direct impact on the various sectors. In fact, the international interest in tourism was not a coincidence, or speculation, but it is based on a firm belief in the international community, including organizations and institutions that tourism through what will be stirred from direct contacts and spontaneous is influenced by the media, between men and women come from different cultures, and follow divergent lifestyles, represent a vital force for peace, and a factor to promote friendship and understanding between the peoples of the world, and the logic of a factor to reconcile environmental protection and economic development, and the fight against poverty in a sustainable manner.